A inclusão do aluno surdo no ensino médio. - Miller Junior, Ademar (2013)
Over the last years the Federal Government has been making progress in the definition and implementation of an educational policy for the deaf, creating laws and programs to put into action this policy. Thus, it is important to monitor the actions taken by the Department of Education at the municipal and state levels in order to discuss the contributions of the legislation for the education of the deaf and the challenges that cross the developed actions. This research aimed to investigate the inclusion of deaf students in secondary school in Espírito Santo, Brazil. In order to support the discussion on the education of the deaf, authors that discuss about this issue were used. For this study, a qualitative study was conducted, which focused on the narratives of young deaf people who attend or attended secondary school recently. The studied narratives showed the importance of discussing three aspects: the level of education of the young deaf before secondary school; the conditions of schooling in secondary school in regular schools; the choice of the profession and the professional practice in the life plans mentioned by these individuals. The narratives of deaf people tell us their life stories in regular schools with the inclusive policy in recent years. This study presents the problem of an education that does not value the experience of deaf people in the school. It also discusses the possibilities of deaf students learn in school for hearers, as well as the vision of each of these individuals about the school routine and their plans for the future. The research shows that the secondary school education did not provide the necessary basis for the deaf students think of their life projects more consistently. The study also reveals some problems that lead to failure the attempts of a better education for deaf people. As a conclusion, the present paper understands that it is urgent the necessity of a reorganization of the inclusive education policy for the deaf. It is important to comprehend that the focus should be neither deafness nor the development in the area, but the understanding of the deaf people, their identity and culture, as well as the implications that the deafness perspective brings on these people and their education.